Mucin4 (MUC4) Gene and Pri–miR146a Expression in Iraqi Females under In Vitro Fertilization Program - Majeed, Israa M.; Almohaidi, Asmaa M. Salih (Iraqi Journal of Science, 2025)
MUC4, a type of reproductive mucus secreted by epithelial cells, can alter the uterine environment and weaken the epithelial lining, making it challenging for an embryo to implant. Furthermore, MUC4 has been linked to mature endometriosis, a condition that affects the uterus. As a result, abnormal mucus production led to female Infertility. The current study evaluates the association between mucin4, pri-miR146a, with Infertility by measuring the fold change in gene expression to improve IVF program in Iraqi medical centres. This was achieved by assessing a new parameter in 128 infertility women under IVF. The study included 84 infertile females: - 26 successful implantations, 58 failure failed implantations under an in vitro fertilization program and 44 fertile females under IVF as control divided into two subgroups, 21 successful implantations and 23 failed implantations. Current work conclusion, the infertility, cases under the IVF program with fertile failure implantation cases related to significant down-regulation of mucin-4, except successful fertile cases recorded significant up-regulation. These results recorded up-regulation of miR-146a-5p gene expression and down-regulation of miR146a-3p expression. There is a significant negative correlation between mucin4 with miR-146a-5p and miR-146a-3p. These relations may influence embryo implantation by regulating mucin4 gene expression under the effect of negative correlation of both 5p and 3p in infertile females undergoing IVF programs.